Use of intelligent sensors and software radio technologies foroptimal design of reconfigurable multimedia surveillance networks. - Sacchi, C. (IEEE Communications magazine)
In these last years, the increasing request for security coming from civil society led to intensive exploitation of the most advanced technological tools for solving problems related to remote monitoring of public sites. New-generation multimedia surveillance systems will be characterized by such key topics as distribution of processing capabilities among intelligent sensor and central processing levels, and dynamic reconfigurability of the wireless links thanks to innovative software radio technologies. In this work a joint analysis of such aspects is presented in order to provide optimal design strategies for new-generation multimedia surveillance networks, able to take into account the trade-offs between available computing and communications resources and required performance in terms of correct event detection and real-time processing